IMPLEMENTATION OF THE WAKALAH BIL UJROH CONTRACT IN FINANCING PRODUCTS AT ISLAMIC FINANCIAL INSTITUTIONS - Auliaurrahman, Muhammad Fikri (JURNAL HAKAM, 2025)
ABSTRACTThis study aims to analyze the implementation of the Wakalah bil ujrah contract in financing products within Islamic financial institutions and to identify the challenges and opportunities in its application. This contract allows financial institutions to act as representatives of customers in conducting specific financial transactions while receiving ujrah (fees) as compensation for the services provided.  This research employs a descriptive qualitative method using literature review techniques and a conceptual approach. The findings indicate that the Wakalah bil ujrah contract is applied in various products, such as Islamic multipurpose financing, home ownership financing (Islamic mortgage/PPR Syariah), vehicle financing, and micro and SME financing and Hajj Financing.  However, its implementation still faces several challenges, including limited public understanding of this contract, differences in regulatory interpretations among Islamic financial institutions, and competition with conventional financing products. To overcome these challenges, efforts such as public education, regulatory harmonization, product innovation, and increased transparency in managing ujrah fees are necessary.Keywords : Wakalah bil ujrah, Islamic Financing, Islamic Financial Institutions, Regulations, Product Innovation. ABSTRAKPenelitian ini ditulis bertujuan untuk menganalisis penerapan akad wakalah bil ujrah dalam produk pembiayaan di lembaga keuangan syariah serta mengidentifikasi tantangan dan peluang dalam implementasinya. Akad ini memungkinkan lembaga keuangan bertindak sebagai wakil nasabah dalam melakukan transaksi keuangan tertentu dengan memperoleh ujrah (fee) sebagai imbalan atas jasa yang diberikan. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik studi literatur dan pendekatan konseptual. Hasil penelitian menunjukkan bahwa akad wakalah bil ujrah diterapkan dalam berbagai produk pembiayaan di LKS yaitu seperti pembiayaan multiguna syariah, pembiayaan kepemilikan rumah (PPR Syariah), pembiayaan kendaraan, pembiayaan usaha mikro dan UKM serta pembiayaan haji. Namun, penerapannya masih menghadapi beberapa tantangan, seperti kurangnya pemahaman masyarakat mengenai akad ini, perbedaan interpretasi regulasi antar lembaga keuangan syariah, serta persaingan dengan produk pembiayaan konvensional. Untuk mengatasi kendala tersebut, diperlukan upaya edukasi masyarakat, harmonisasi regulasi, inovasi produk, serta peningkatan transparansi dalam pengelolaan biaya ujrah.Kata Kunci: Wakalah bil ujrah, Pembiayaan Syariah, Lembaga Keuangan Syariah, Regulasi, Inovasi Produk.